2020
DOI: 10.21105/astro.2007.07253
|View full text |Cite
|
Sign up to set email alerts
|

The impact of signal-to-noise, redshift, and angular range on the bias of weak lensing 2-point functions

Abstract: Weak lensing data follow a naturally skewed distribution, implying the data vector most likely yielded from a survey will systematically fall below its mean. Although this effect is qualitatively known from CMB-analyses, correctly accounting for it in weak lensing is challenging, as a direct transfer of the CMB results is quantitatively incorrect. While a previous study (Sellentin et al. 2018) focused on the magnitude of this bias, we here focus on the frequency of this bias, its scaling with redshift, and its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A comparison of these figures shows that the probability distribution of ξ ± (θ) for the largest values of θ deviates from a Gaussian, while this is not the case for band powers and COSE-BIs. Louca & Sellentin (2020) also showed that the COSEBI likelihood is well approximated by a Gaussian for a survey such as KiDS. For our fiducial analysis we employ the angular ranges shown in Fig.…”
Section: Scale Sensitivity Of the Two-point Statisticsmentioning
confidence: 92%
“…A comparison of these figures shows that the probability distribution of ξ ± (θ) for the largest values of θ deviates from a Gaussian, while this is not the case for band powers and COSE-BIs. Louca & Sellentin (2020) also showed that the COSEBI likelihood is well approximated by a Gaussian for a survey such as KiDS. For our fiducial analysis we employ the angular ranges shown in Fig.…”
Section: Scale Sensitivity Of the Two-point Statisticsmentioning
confidence: 92%
“…The DES 3x2pt analysis, described in Krause & Eifler et al, (2017), adopts a Gaussian likelihood for the 3x2pt data vector (see, e.g., Sellentin & Heavens 2018;Louca & Sellentin 2020, for a discussion of this approximation). The Gaussian likelihood, L, is determined by the expectation value of the data vector at parameters Θ, (Θ), and by a covariance matrix C,…”
Section: Des Y1 Likelihood and Ppd Testsmentioning
confidence: 99%
“…Since the dependence structure in a multivariate Gaussian distribution is also fully described by its covariance matrixsuch that the components of a multivariate Gaussian with diagonal covariance are independent -removing linear correlations removes all Gaussian dependence. This whitening follows the same process as Sellentin & Heavens (2018), , Diaz Rivero & Dvorkin (2020) and Louca & Sellentin (2020): each pair of data elements is whitened separately using a Cholesky whitening procedure followed by a mean subtraction. The result is a whitened pair having a mean of zero and a covariance matrix of the identity matrix.…”
Section: Mutual Informationmentioning
confidence: 99%
“…Transcovariance is a measure of non-Gaussianity of a distribution introduced in Sellentin & Heavens (2018) and subsequently used in , Louca & Sellentin (2020) and Diaz Rivero & Dvorkin (2020). We will follow the latter three papers in considering only the additive transcovariance 𝑆 + , which is defined as…”
Section: Transcovariancementioning
confidence: 99%
See 1 more Smart Citation